Heparanase-Dependent Remodeling of Initial Lymphatic Glycocalyx Regulates Tissue-Fluid Drainage During Acute Inflammation in vivo - Arokiasamy, Samantha; King, Ross; Boulaghrasse, Hidayah; Poston, Robin N.; Nourshargh, Sussan; Wang, Wen; Voisin, Mathieu-Benoit (Frontiers in Immunology, 2019)
The glycocalyx is a dense layer of carbohydrate chains involved in numerous and fundamental biological processes such as cellular and tissue homeostasis, inflammation and disease development. Composed of membrane-bound glycoproteins, sulfated proteoglycans and glycosaminoglycan side-chains, this structure is particularly essential for blood vascular barrier functions and leukocyte diapedesis. Interestingly, whilst the glycocalyx of blood vascular endothelium has been extensively studied, little is known about the composition and function of this glycan layer present on tissue-associated lymphatic vessels (LVs). Here, we applied confocal microscopy to characterize the composition of endothelial glycocalyx of initial lymphatic capillaries in murine cremaster muscles during homeostatic and inflamed conditions using an anti-heparan sulfate (HS) antibody and a panel of lectins recognising different glycan moieties of the glycocalyx. Our data show the presence of HS, α-D-galactosyl moieties, α2,3-linked sialic acids and, to a lesser extent, N-Acetylglucosamine moieties. A similar expression profile was also observed for LVs of mouse and human skins. Interestingly, inflammation of mouse cremaster tissues or ear skin as induced by TNF-stimulation induced a rapid (within 16hrs) remodelling of the LV glycocalyx, as observed by reduced expression of HS and galactosyl moieties, whilst levels of α2,3-linked sialic acids remains unchanged. Furthermore, whilst this response was associated with neutrophil recruitment from the blood circulation and their migration into tissue-associated LVs, specific neutrophil depletion did not impact LV glycocalyx remodelling. Mechanistically, treatment with a non-anticoagulant heparanase inhibitor suppressed LV HS degradation without impacting neutrophil migration into LVs. Interestingly however, inhibition of glycocalyx degradation reduced the capacity of initial LVs to drain interstitial fluid during acute inflammation. Collectively, our data suggest that rapid remodelling of endothelial glycocalyx of tissue-associated LVs supports drainage of fluid and macromolecules but has no role in regulating neutrophil trafficking out of inflamed tissues via initial LVs.